An inter-hemispheric seasonal comparison of polar amplification using radiative forcing of a quadrupling CO2 experiment - Casagrande, Fernanda; Buss de Souza, Ronald; Nobre, Paulo; Andre Lanfer Marquez (Annales geophysicae (1988), 2020)
The numerical climate simulations from the Brazilian Earth System Model (BESM) are used here to investigate the response of the polar regions to a forced increase in CO2 (Abrupt-4×CO2) and compared with Coupled Model Intercomparison Project phase 5 (CMIP5) and 6 (CMIP6) simulations. The main objective here is to investigate the seasonality of the surface and vertical warming as well as the coupled processes underlying the polar amplification, such as changes in sea ice cover. Polar regions are described as the most climatically sensitive areas of the globe, with an enhanced warming occurring during the cold seasons. The asymmetry between the two poles is related to the thermal inertia and the coupled ocean–atmosphere processes involved. While at the northern high latitudes the amplified warming signal is associated with a positive snow– and sea ice–albedo feedback, for southern high latitudes the warming is related to a combination of ozone depletion and changes in the wind pattern. The numerical experiments conducted here demonstrated very clear evidence of seasonality in the polar amplification response as well as linkage with sea ice changes. In winter, for the northern high latitudes (southern high latitudes), the range of simulated polar warming varied from 10 to 39 K (-0.5 to 13 K). In summer, for northern high latitudes (southern high latitudes), the simulated warming varies from 0 to 23 K (0.5 to 14 K). The vertical profiles of air temperature indicated stronger warming at the surface, particularly for the Arctic region, suggesting that the albedo–sea ice feedback overlaps with the warming caused by meridional transport of heat in the atmosphere. The latitude of the maximum warming was inversely correlated with changes in the sea ice within the model's control run. Three climate models were identified as having high polar amplification for the Arctic cold season (DJF): IPSL-CM6A-LR (CMIP6), HadGEM2-ES (CMIP5) and CanESM5 (CMIP6). For the Antarctic, in the cold season (JJA), the climate models identified as having high polar amplification were IPSL-CM6A-LR (CMIP6), CanESM5(CMIP6) and FGOALS-s2 (CMIP5). The large decrease in sea ice concentration is more evident in models with great polar amplification and for the same range of latitude (75–90∘ N). Also, we found, for models with enhanced warming, expressive changes in the sea ice annual amplitude with outstanding ice-free conditions from May to December (EC-Earth3-Veg) and June to December (HadGEM2-ES). We suggest that the large bias found among models can be related to the differences in each model to represent the feedback process and also as a consequence of each distinct sea ice initial condition. The polar amplification phenomenon has been observed previously and is expected to become stronger in the coming decades. The consequences for the atmospheric and ocean circulation are still subject to intense debate in the scientific community.